AMANAH DAN KHIANAT DALAM AL-QUR’AN MENURUT QURAISH SHIHAB - Andika, Titin; Taqiyuddin, Muhammad; Yunita, Nurma (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
This study aims to reveal the concept of trust and betrayal in the Qur’an based on the perspective of tafsir al-Misbah by Quraish Shihab. This is library study and applies a content analysis. This study concludes that when a person swears or says something in the name, nature, or deed of Allah, but not in the name of other than Him, then he must fulfill it in a way that his words are aligned with his deeds, and he should be able to keep what has been entrusted to him, the so-called trust. If speech does not conform to the deeds, and one is unable to maintain the trust put in him, this is what is called betrayal. Such acts are of the characteristics of hypocrites and will be the path for them (those who commit betrayal) to hell. In order to avoid such acts of betrayal, humans should follow the Qur’anic instructions as their life’s guidance for the sake of achieving happiness in this world and the hereafter.Keywords: Trust, Betrayal, the Qur’an, Quraish Shihab